2013
DOI: 10.1007/s00134-013-3036-3
|View full text |Cite
|
Sign up to set email alerts
|

An increased alveolar CD4 + CD25 + Foxp3 + T-regulatory cell ratio in acute respiratory distress syndrome is associated with increased 30-day mortality

Abstract: An increased T-regulatory cell ratio in the admission BAL of patients with ARDS is an important and independent risk factor for 30-day mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 28 publications
6
80
2
Order By: Relevance
“…These authors also showed a higher mortality rate using T-regs knockout mice, due to persistent lung inflammation. Recently, a clinical study from Germany showed an increase in the T-cell subset ratio only, i.e., an augmentation of T-regulator cells/all CD4 T-cells, in 47 ARDS patients compared to eight controls requiring abdominal surgery for cancer [31]. Similar trends were observed in our study, without reaching significance (p=0.11, data not shown).…”
Section: Discussionsupporting
confidence: 65%
“…These authors also showed a higher mortality rate using T-regs knockout mice, due to persistent lung inflammation. Recently, a clinical study from Germany showed an increase in the T-cell subset ratio only, i.e., an augmentation of T-regulator cells/all CD4 T-cells, in 47 ARDS patients compared to eight controls requiring abdominal surgery for cancer [31]. Similar trends were observed in our study, without reaching significance (p=0.11, data not shown).…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, a deficiency of CD4+ CD25+ FoxP3+ T regulatory cells has been suggested to be a first-hit risk factor for TRALI, using a murine model of antibody-mediated TRALI [13]. In contrast, alveolar CD4+ CD25+ FoxP3+ T regulatory cells were reported to be increased in ARDS patients, with a concomitant correlation with increased IL-10 levels [74]. It will be important to more firmly establish the role T regulatory cells and IL-10 in both ARDS and TRALI.…”
Section: Discussionmentioning
confidence: 99%
“…70,71 Given their limited numbers, Tregs have been shown to become highly proliferative after lung inflammation and are a key feature in controlling exuberant immune responses. 65,72 Ongoing clinical trials are evaluating the role of Tregs in solid-organ transplantation. 73 Studies by Neujahr et al and Bhorade et al have shown that a decreased proportion of Foxp3 + cells among CD4 cells in bronchoalveolar lavage (BAL) can potentially predict worse lung allograft outcome and help guide therapeutic immunosuppression in lung transplant recipients.…”
Section: Resolution and Repair Mechanismsmentioning
confidence: 99%